Predicting Fluency With Language Proficiency, Working Memory, and Directionality in Simultaneous Interpreting - Lin, Yumeng; Lv, Qianxi; Liang, Junying (Frontiers in Psychology, 2018)
Simultaneous interpreting is a complex bilingual verbal activity that poses great challenges for working memory and language proficiency. Fluency is one of the crucial indicators in evaluating simultaneous interpreting quality, the violation of which is characterized by disfluency indicators such as interruptions, hesitations, repetitions, corrections and blanks. To uncover factors underlying fluency in simultaneous interpreting, 22 interpreting students performed a battery of tasks to test their language proficiency and working memory. Two simultaneous interpreting tasks, both from Chinese to English and from English to Chinese, were also conducted, and fluency was evaluated according to the five indicators. Two factors (language proficiency and working memory) and the five objectively measured disfluency indicators were then used as input for a regression analysis in both directions to model factors underlying fluency in simultaneous interpreting performance. The results reveal that, with fluency measured as a whole, working memory and directionality yield a significant effect on fluency, and that working memory is the only variable that predicts fluency in both directions, accounting for 50% and 51% of the variation in the occurrence of disfluencies in Chinese-English and English-Chinese interpreting respectively. The findings clarify for the first time the role of language proficiency, working memory and directionality upon fluency in simultaneous interpreting, indicating the critical role of working memory capability as compared with language skills in fluent production. The research also supports the position that, for interpreting students, interpreting performance tends to be more fluent in the non-native to native language direction.